Combining Multiple Markers in Environmental DNA Metabarcoding to Assess Deep-Sea Benthic Biodiversity - Liu, Jun; Zhang, Haibin (Frontiers in Marine Science, 2021)
Environmental DNA (eDNA) metabarcoding is an emerging tool to estimate diversity by combining DNA from the environmental samples and the high-throughput sequencing. Despite its wide use in estimating eukaryotic diversity, many factors may bias the results. Maker choice and reference databases are among the key issues in metabarcoding analyses. In the present study, we compared the performance of a novel 28S rRNA gene marker designed in this study and two commonly used 18S rRNA gene markers (V1-2 and V9) in estimating the eukaryotic diversity in the deep-sea sediments. The metabarcoding analyses based on the sediment surveys of the Okinawa Trough found that more eukaryotic taxa were discovered by 18S V9 than 28S and 18S V1-2, and that 18S V9 also performed better in metazoan recovery than the other two markers. Although a broad range of taxa were detected by the three metabarcoding markers, only a small proportion of taxa were shared between them even at the phylum level. The NMDS analysis also supported that communities detected by the three markers were distinct from each other. In addition, different communities were resolved by different reference databases (NCBI nt vs. SILVA) for the two 18S markers. Combining the three markers, annelids were found to be the most abundant (44.9%) and diverse (179 OTUs) metazoan group in the sediments of the Okinawa Trough. Therefore, multiple independent markers are recommended to be used in metabarcoding analyses during marine diversity surveys, especially for the poorly understood deep-sea sediments.